IMPACT OF ABCB1 AND CES1 GENETIC POLYMORPHISMS ON TROUGH STEADY-STATE DABIGATRAN CONCENTRATIONS IN PATIENTS AFTER ENDOPROSTHESIS OF KNIFE JOIN - D. A. Sychev; A. N. Levanov; T. V. Shelekhova; P. O. Bochkov; N. Р. Denisenko; K. A. Ryzhikova; K. В. Mirzaev; E. A. Grishina; M. A. Gavrilov («REMEDIUM GROUP» Ltd., 2018)
Oral anticoagulants are widely used to prevent thromboembolic events in patients following total knee arthroplasty [1]. The genetic characteristics of patients affect the efficacy and safety of anticoagulants [2]. Dabigatran etexilate is a direct inhibitor of thrombin used as a prophylaxis of venous thromboembolic events (VTE) in Europe and Russia. [3]. This study evaluated the impact of ABCB1 and CES1 genetic polymorphisms on the peak and residual dabigatran concentration in orthopedic patients. Material and methods: A total of 30 patients aged 43 to 77 years following knee joint replacement were enrolled in the study. All patients received dabigatran etexilate at a dose of 220 mg/day for the prevention of VTEO. ABCB1 and CES1 genetic polymorphism genotyping was performed by real-time polymerase chain reaction (PCR). The peak and residual concentrations of dabigatran were determined by high-performance liquid chromatography (HPLC). Results: It was found that the ТТ genotype of the MDR1 gene С3435Т polymorphism is associated with a higher peak concentration of dabigatran than the CC genotype (p <0.1). Statistically significant results for CES1 gene rs2244613 polymorphism were obtained in patients younger than 60 years (p <0.05). The analysis of the haplotypes combination in two polymorphisms showed that the most common haplotype combination CC (rs1045642) ABCB1/CT (rs2244613) CES1 was significantly associated with a higher peak concentration of dabigatran compared to the rest of haplotype combinations (p = 0.002). Conclusions: The examination of a cohort of patients receiving dabigatran for the prevention of VTE during the period of large joints arthroplasty showed that SNPs C3435T ABCB1 and rs2244613 CES1 could play an important role in changing dabigatran concentrations. No data suggestive of the impact of SNP ABCB1 rs4148738 on the peak concentration of dabigatran were received.